ACADEMIC MOBILITY OF FOREIGN STUDENTS IN THE CONDITIONS OF THE NATIONAL POLICY OF THE STATE - Akbayeva, G.N.; Beregovaya, O.A. (Халықаралық ғылыми форум МАТЕРИАЛДАРЫ 6–8 сəуір, 2016)
The question of academic mobility of foreign students in a multicultural and multilingual society in Kazakhstan was studied; the national policy of the state, as well as the main stages of studied phenomenon development was analyzed.
Keywords: академическая мобильность; студенты-иностранцы; национальная политика; евразийство; полиязыковая среда; интернационализация; academic mobility; foreign students; national policy; Eurasianism; multilingual environment; internationalization